THE CONCEPT OF DIVERSITY MANAGEMENT IN ENSURING THE DEVELOPMENT OF THE MARKET POTENTIAL OF THE ENTERPRISE IN CRISIS CONDITIONS - STADNYK, Valentyna; КRASOVSKYI, Oleksandr; SHKLJAR, Jevhenij; FURMAN, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the war-induced problems of formation and realization of the market potential of subjects of the entrepreneurial sector of the national economy. Based on the analysis of scientific views on the essential content of the definition "market potential of the enterprise", it was concluded that they are dominated by the marketing component of work with the market, which limits management decisions regarding the development of market potential to the sphere of work with consumers. The need to expand this interpretation towards the assessment of the economic feasibility of decisions is argued, which makes it possible to more effectively manage the processes of its expansion, including through the implementation of measures that make it possible to ensure its development, relying on the support of a wider range of stakeholders. The author's position regarding the management of the processes of building up and developing the market potential of the enterprise based on the concept of "diversity management" was formed. In the light of this concept, the definition of an enterprise is presented as a socio-economic system, designed taking into account the diversity of factors of the external environment and with a rationally justified (from the point of view of the goals of effective functioning) set of structural elements and a system of connections between them, which provides the necessary for the creation of products (services ) the level of diversity, efficiency and effectiveness of technological and management processes aimed at creating consumer values, taking into account the diversity of consumer preferences in selected market segments. This made it possible to outline the spheres and directions of enrichment of diversity in the structure of resources, processes and target markets for the development of the market potential of the enterprise. It is noted that the key sign of the expediency of increasing the level of diversity in the structure of resources, processes and target markets should be the ability of the enterprise to create new consumer values. The importance of developing cooperation with all groups of stakeholders in the field of innovative design of consumer values and technological equipment of innovative business processes is emphasized.
Keywords: entrepreneurship; business market potential; economic feasibility; areas of diversity development; consumer value; innovation; stakeholder interaction